Northwest Russian Forestry in a Nutshell - Karvinen, Sari; Välkky, Elina; Torniainen, Tatu; Gerasimov, Yuri (Finnish Forest Research Institute, 2006)
The purpose of the paper is to provide a general view of the current state of the forest sector in Northwest Russia. The paper is a translation of the Finnish guidebook on forestry in Northwest Russia "Luoteis-Venäjän metsätalouden taskutieto", which was published at the Finnish Forest Research Institute in spring 2005. Some small updating and alterations have been made since the publishing of the guidebook in Finnish in 2005, but generally the paper presents the most current information available at the time of writing the Finnish version. The paper studies the basics of Russian forestry, covering themes from forest resources to their management and utilisation. The ongoing renewal pertaining to the forest legislation and administration will lead to changes in forest sector, which may deviate greatly from the plans predicted at the time of writing the publication. Thus, the courses of the changes are presented rather briefly. In the chapter about forest utilisation the allowable and actual cuts for different regions of Northwest Russia are given and the guidelines for forest utilisation are described. The logging methods and Russian harvesting technology are presented briefly. In the chapter about forest industry the annual production figures and locations of production plants for sawmill and wood-based panel industry as well as for chemical forest industry are given. In addition, the competitiveness, investments and foreign trade of Russian forest industry are discussed.Further information on topical events may be obtained in Finnish on the internet service of Expertise in Russian Forestry -project at www.idanmetsatieto.info.